Práticas investigativas na Educação Infantil: construindo diálogos com a Educação em Ciências - Elessandra Helena Ribeiro (2023)
In this work I narrate and analyze the investigative practices experienced throughout the development of the Birds project with a class of 5-year-old children at a private school in Belo Horizonte. Through my report on this experience, I sought to identify the interactions experienced by the group and reflect on the meanings they made possible to construct throughout the project. Furthermore, it was possible to reflect on the teacher's mediations during the children's investigations and discuss the potential of nature investigation for the training of children in Early Childhood Education. Thus, through this research I sought to expand the discussion in this little explored field and reflect on the practice of Science themes in Early Childhood Education based on work with research projects. The research started from affiliation with the field of narrative research within the category of narratives of lived experiences or narratives of educational experience, seeking to establish a link between the memories of the lived experience and how they connect with the researcher's current experience. The main sources of research were the photos that record the entire development path of the Birds project and the researcher's memories that are activated when she reviews these images. In addition to photos and memories, a book recording the research findings with children constitutes a source of memory to help narrate and analyze this experience. These artifacts constitute the methodological tools of this field research. Narrating what I experienced gave me the possibility of reflecting to give new meaning to my daily practice with children and transforming everyday school life based on remarkable experiences.